Unibody design for aortic disease with a narrow aortic bifurcation: Tips and tricks for success - Yoshida, Ricardo de Alvarenga [UNESP]; Costa, Renato Fanchiotti; Cunha, Débora Ortigosa; Palhares, Rafael Mendes; Jaldin, Rodrigo Gibin [UNESP]; Sobreira, Marcone Lima [UNESP]; Pimenta, Rafael Elias Farres [UNESP]; Yoshida, Winston Bonetti [UNESP] (FapUNIFESP (SciELO), 2021)
Background: Surgical management of patients with abdominal aortic diseases associated with distal narrowing is a challenging situation. Objectives: To evaluate outcomes of unibody bifurcated endovascular stent graft repair. Methods: This is a retrospective, observational, multi-institutional database study of a cohort of consecutive cases, approved by the local Ethics Committee. Records were reviewed of patients diagnosed from 2010 to 2020 with “shaggy” aorta, saccular aneurysm, penetrating aortic ulcer, and isolated aortic dissection located in the infrarenal abdominal aorta. All patients were treated with a unibody bifurcated stent graft. Main outcomes were technical success, procedure complications, long-term patency, and mortality in the follow-up period up to 5 years. Data on demographics, comorbidities, surgical management, and outcomes were analyzed. Results: Twenty-three patients were treated with unibody bifurcated stent graft repair, including 7 cases of “shaggy” aorta, 3 isolated dissections of the abdominal aorta, 4 penetrating aortic ulcers, and 9 saccular aneurysms. Immediate technical success was achieved in 100% of cases. At follow-up, all stent grafts remained patent and there were no limb occlusions. The patients were symptom-free and reported no complications related to the procedure. There were 5 deaths during the follow-up period (median= 4 years), but none were related to the procedure and there were no aorta-related deaths. Conclusions: The present study shows that unibody bifurcated stent grafting is safe and effective in this group of patients with narrow distal abdominal aorta and complex aortic pathology. The results were similar for both infrarenal aortic aneurysms and aorto-iliac atherosclerotic disease.
Design unimodular para doença da aorta com bifurcação aórtica estreita: Dicas para o sucesso
Keywords: Abdominal aorta; Aneurysm; Aortic diseases; Endovascular procedures; Saccular aneurysm